REGISTER AKTIVITAS PENYADAP KARET MASYARAKAT MELAYU SAMBAS DI DESA SEMATA KABUPATEN SAMBAS: KAJIAN SOSIOLINGUISTIK - Ayu Annisa; Ahadi Sulissusiawan; Mellisa Jupitasari (Universitas Tanjungpura, 2022)
The discussion of the problem of this study includes the type of register, and the function of the register, what factors influence the use of rubber tapper registers in speech rubber tapper Malay Sambas community in the Semata village, Sambas Regency. The purpose of this study to describe the type, function, and register factors rubber tapper Malay Sambas community in the Semata village, Sambas Regency based on sociolinguistic studies. This study uses qualitative methods. The source of this data is Malay Sambas spoken by informants in Semata village, Sambas Regency. This research use competent and free listening techniques, recording techniques, recording techniques, and interview techniques. Based on the overall data that has been analyzed, there are 25 registers used by rubber tappers, the type of closed registers amounted to 14 registers and open registers amounted to 11. Instrumental register functions totaled 16 registers, regulatory functions totaled 9, representational functions totaled 8, interactional functions totaled 4, Personal functions totaled 3, and heuristic functions totaled 8 on rubber tapper Malay Sambas community in the Semata village, Sambas Regency. Factors affecting the use of registers amounted to 8 namely, setting, participant, ends, act, key, instrumentalities, norms, dan genre.